Wahyu Risky Nurpitasari THE EFFECT OF BRACING SHAPE VARIATIONS (Z-BRACE AND X-BRACE) ON ENERGY DISSIPATION DUE TO CYCLIC LOADING IN COLD-FORMED STEEL FRAMES: The Effect of Bracing Shape Variations (Z-Brace And X-Brace) on Energy Dissipation Due to Cyclic Loading in Cold-Formed Steel Frames - Wahyu Risky Nurpitasari; Nindyawati; B. Sri Umniati (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2026)
This study investigates the effect of bracing-shape variations—specifically Z-braces and X-braces—on the energy dissipation capacity of cold-formed steel (CFS) portal frames under cyclic loading. The research was conducted experimentally at the Structural Engineering Laboratory, Department of Civil Engineering, Universitas Negeri Malang, using hollow box CFS profiles (G550 grade, 40×40×0.3 mm). Three configurations were tested: non-braced (No-Brace), X-braced, and Z-braced frames. Cyclic static loading was applied in accordance with ASTM E2126-11 to evaluate lateral strength, energy dissipation, and failure mechanisms. The results show that adding bracing significantly increases lateral load capacity compared to the unbraced frame. The X-brace specimen demonstrated the highest lateral strength of 1.808 kN, nearly double that of the No-Brace configuration (0.898 kN), followed closely by the Z-brace (1.825 kN). In terms of energy dissipation, the X-brace achieved the highest value of 743.61 kN·mm, approximately 79.5% higher than No-Brace and 165.7% higher than Z-Brace, indicating superior hysteretic performance. Structural failures primarily occurred at screw joints due to cyclic shear and pull-out effects. Overall, the study concludes that X-brace configurations provide the most effective enhancement in both lateral stiffness and seismic energy dissipation capacity for cold-formed steel portal frames. At the same time, Z-braces exhibit better ductility but lower energy absorption efficiency. These findings are expected to contribute to the design of lightweight, earthquake-resistant cold-formed steel structures. Keywords: Cold-formed steel; Bracing configuration; X-brace, Z-brac; Cyclic loading; Energy dissipation; Structural performance.